Supratentorial and spine metastatic medulloblastoma in adults - Satriya Ranuwibawa; Nyoman Wahyudana (Neurologico Spinale Medico Chirurgico, 2021)
Medulloblastoma is an infratentorial primitive neuroectodermal tumor that is predominantly found in children. The incidence of medulloblastoma fluctuates between 20-35% in kids and is extraordinarily uncommon to be found in adults. A twenty-four-year-old man presented with a chief complaint of weakness of the lower extremity. Physical examination revealed myelopathy sign at the 12th thoracic level. Past medical history revealed that he had undergone total resection of a medulloblastoma of the cerebellum three years prior to the weakness. A thoracolumbar MRI with gadolinium contrast injection was performed which revealed a solid mass at thoracic vertebra 12 – lumbar 1. Four months after the total resection of the spinal mass, the patient presented again with a chief complaint of vomiting and a severe headache. A head CT scan was done followed by a head MRI with gadolinium contrast injection. A mass was found at the right temporoparietal region and craniotomy for tumor removal was immediately done to resolve the intracranial pressure problem. Pathological anatomy revealed the spinal and intracranial mass as medulloblastoma. This case report presents an adult with primary medulloblastoma of the cerebellum who presented with metastases of the spine and supratentorial regions. However, the incidence of medulloblastoma is very rare in adults and the 5-year survival rate is between 60% - 80% for all adult medulloblastoma patients. Surgeons must be careful in choosing the first management for better prognosis such as surgical management only, surgical management followed by adjuvant therapy, or just a chemotherapeutic-only approach.